2014
DOI: 10.3310/hsdr02130
|View full text |Cite
|
Sign up to set email alerts
|

Networked innovation in the health sector: comparative qualitative study of the role of Collaborations for Leadership in Applied Health Research and Care in translating research into practice

Abstract: BackgroundCollaborations for Leadership in Applied Health Research and Care (CLAHRCs) were an initiative of the National Institute for Health Research in response to a new research and development strategy in the NHS: ‘Best Research for Best Health’. They were designed to address the ‘second gap in translation’ identified by the Cooksey review; namely, the need to improve health care in the UK by translating clinical research into practice more effectively. Nine CLAHRCs, each encompassing a university in partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 122 publications
0
10
0
2
Order By: Relevance
“…15 Funded by the National Institute for Health Research (NIHR), the first round of five CLAHRCs was established in 2009. Evaluation demonstrated that the first wave had differing capabilities with respect to reducing the ‘know-do’ gap, partly because of differing interpretations and enactments of their mission 16. However, success in this area will inevitably require a long-term, sustained focus on relationship building, resource allocation and, in some cases, culture change 17.…”
Section: Introductionmentioning
confidence: 99%
“…15 Funded by the National Institute for Health Research (NIHR), the first round of five CLAHRCs was established in 2009. Evaluation demonstrated that the first wave had differing capabilities with respect to reducing the ‘know-do’ gap, partly because of differing interpretations and enactments of their mission 16. However, success in this area will inevitably require a long-term, sustained focus on relationship building, resource allocation and, in some cases, culture change 17.…”
Section: Introductionmentioning
confidence: 99%
“…This study is timely because of the increasing use of KIT roles by AHSNs and partnerships, 60 and the relative lack of evidence for their effectiveness, 94 although the literature on knowledge brokers has grown significantly in the last few years with the publication of evaluations of CLAHRCs 39,42,44,60,245,250,251 and other initiatives. 90 The complexity of the role and the environment in which it is played out justifies the need for more research on knowledge brokers.…”
Section: Discussionmentioning
confidence: 99%
“…Such linkages can also support knowledge mobilisation and coproduction if conducted in a meaningful manner. 7 CLAHRCs have demonstrated an increase in social networks, partnerships and 'relational capability' enabled by leadership, 15 and our experience is that these networks support successful funding applications.…”
Section: Linkages and Collaborationsmentioning
confidence: 97%
“…It can also be made possible through 'matched funding' arrangements where all types of collaborating organizations offer resource such as time, facilities or fee waivers into the collaboration free of charge to the research partnership. The relatively long-term funding period of the CLAHRC (5 years for each term) has provided an on-going academic and practice infrastructure 15 and opportunities for iterative learning embedded in special interest groups, steering and advisory groups 2 and CoPs.…”
Section: Infrastructurementioning
confidence: 99%